Effects of Constraint-induced Movement Therapy on Patients with Post-cerebrovascular Disease Hemiplegia in the Maintenance Phase: Evaluation of Gait Improving Effects by Biomechanical Analysis - Okuda, Shosaku; Tanabe, Hirofumi; Tanabe, Hiroshi; Ryoya, Shibasaka; Sakurai, Yoshimi; Takata, Yuichi (British Journal of Healthcare and Medical Research, 2025)
In this study, a series of constraint-induced movement therapy for the lower extremity (LE-CIMT) was performed on patients with post-stroke hemiplegia, and biomechanical analyses were conducted on the effective changes in their gait to examine if any long-term improvement in walking functions was observed. Participants were seven patients with hemiplegia (five men and two women) in their maintenance phase who were independent in their daily lives. Assessments using Fugl-Meyer Assessment (FMA)-Lower Extremity, FMA-Balance, 10-Meter Walking Test If possible, please give the version of the software here. For example, this information could be Nexus 2.14 or Nexus 2.16. (10MWT), and Time Up and Go Test (TUG) were conducted at 1) five weeks before intervention (baseline); 2) before therapy implementation on Day 1 of intervention (pre); 3) on the final day of intervention period [two weeks: post (2w)], and 4) on the day 16 weeks after the Day 1 of intervention [post (16w)], respectively. In addition, joint angles (at hip and ankle joints) and joint moment (at ankle joint) were measured at baseline and post (2w) using a three-dimensional motion analysis software (Nexus 2.12.1, Vicon Motion Systems Ltd, Oxford, UK) and a ground reaction force measurement device (AMTI BP400600, Advanced Mechanical Technology, Inc., Massachusetts, USA). The results indicated significant differences after the intervention, exhibiting an increase in hip joint extension angle, ankle joint dorsiflexion angle, and ankle joint plantar flexion moment on participants' paralyzed side extremities. Participants' gait propulsion on the paralyzed side also exhibited improvement from the angle increases, indicating evident improvements in 10MWT and TUG and suggesting that the effects of LE-CIMT were associated with the long-term effects observed in the participants.